The Implementation of Profile Matching Method in the Employee Appointment Assessment Process at PT. Primarindo Argatile: Penerapan Metode Profile Matching dalam Proses Penilaian Pengangkatan Karyawan Tetap di PT. Primarindo Argatile - Darip, Mochammad; Rudianto; Rakhim Setya Permana, Basuki; Auliana, Sigit (Pustabiblia: Journal of Library and Information Science, 2024)
In the midst of economic competition and the global trading system which is the influence of advances in information technology, companies must review the use of the number of workers for the sake of efficiency in the company's expenses. Employees are company assets that can be controlled by the number of uses and work systems. The development of science and technology has given rise to new methods or models and concepts that can be adapted to company business processes, one of which is decision support systems. PT. Primarindo Argatile is a company that produces several types of ceramics under the Red Hourse trademark. There are two categories for work agreement status, namely the contract employee status category and the permanent employee status category. Problems occur when management wants to promote or appoint permanent employees as replacements for employees who have retired or resigned. Based on the system analysis and primary data collection that researchers used in this research, one of the reasons is that they have not used an assessment approach or method as a support in making decisions that suit their needs, and one of the recommendations for overcoming several problems related to assessment system techniques and procedures is to use an approach. profile matching method. This method is expected to minimize assessment criteria from subjective factors and perspectives by measuring and exploring the similarity of candidate profiles in accordance with the ideal profile determined using a Likert scale. The weighting scale in the assessment system, company management places greater emphasis on three aspects of work achievement, namely work quality, work quantity and work loyalty. Calculating the final results using the profile matching method approach can show recommendations from several candidates based on the results of an exploratory analysis of employee profiles from three similarity values of 80% core factors and 20% secondary factors.